Analysis of the Relationship of Risk and Return Using the Capital Asset Pricing Model (CAPM) Method at Kompas 100 for the 2015-2019 Period - Andini Nurwulandari (International Journal of Science and Society, 2020)
This research aimed to investigate the relationship between risk and return on Kompas 100 shares using the Capital Asset Pricing Model (CAPM) approach from 2015 to 2019. The sample amounted to 52 companies registered in Kompas 100. This study used a quantitative approach. The data used includes the closing price of shares and the Composite Stock Price Index (IHSG) for 4 years (1 January 2015 - 31 December 2019) and the risk-free rate, which is calculated using the interest rate on Bank Indonesia Certificates ( SBI) issued by the Bank Indonesia. The results of testing the relationship with the simple correlation coefficient of CAPM calculation, Beta, and CAPM predicted return has a significant positive relationship. If beta increases, the expected return will increase, and vice versa. If Beta goes down, the expected return will go down. Of the 52 sample companies, 33 companies deserve to be used as investment destinations and purchase their shares.